PENGARUH PENGGUNAAN TAWAS PADA PAKAN TERHADAP TOKSISITAS DAN KADAR ALUMINIUM ORGAN TIKUS IN VIVO - Nurrahman -; Retno Murwani; Nur Yazid (Jurnal Pangan dan Gizi, 2012)
The use of tawas as an food additive has widely used in processing, such as the manufacture of smoked fish, salted eggs and meatballs. This study aims to determine the effect of using tawas as addition in food processing to health. There are two groups of mice each containing 11 mice, one group was givena diet that has been given 0.8 percent tawas and the other one was given diet without the addition of tawas (control group). The issue of diet and water is by ad libitum conducted in 30 days. During the experiment it was recorded the feed intake, performance (behavioral), the appearance of the skin, eyes,feces and urine, and body weight. After the maintenance mice were killed, then conducted an analysis of organ weight and levels of aluminum organ. There was a tendency of tawas addition on feed causing less consumption and weight loss on mice. Granting tawas to treated rats showed no differences inphysical appearance of behavior, skin, eyes and feces, and also no differences in organ weight. While there are differences appear in the urine, which treated rats urine looks a bit turbid than the other one.There is deposits of aluminum in organs like heart, liver, lung, pancreas, kidney and bone. Deposit aluminum at pancreas is the most than the other organs. There are not found any clinical symptoms in both control and treated rats. Key words= Alum, toxicity, aluminium